Optimalisasi Pemeriksaan Kesehatan Gratis Berbasis Digital bagi Masyarakat di Timor Tengah Selatan - Jennie Luisa Boboy; Christina Nayoan; Noorce Berek; Roberth Olivianus Asbanu (GOTAVA, 2025)
Free Health Examination (FHE) program is a strategic government initiative aimed at improving community access to promotive and preventive health services. This community service activity was conducted in Timor Tengah Selatan Regency and involved 30 participants from various age groups, ranging from newborns to the elderly. The implementation methods included target identification, cross-sectoral coordination, socialization, direct health examinations at UPT. Puskesmas Siso, and education on the use of the SATUSEHAT Mobile application. Services provided included blood pressure checks, blood glucose measurements, body temperature, pulse, respiration assessments, screening for non-communicable diseases, and special newborn examinations. The results showed active community participation, with 100% of participants completing all examination and education stages. Furthermore, 85% of participants demonstrated increased knowledge regarding the importance of early disease detection and the use of the SATUSEHAT Mobile application. These findings indicate that the FHE program is effective in encouraging healthy lifestyle changes and strengthening collaboration between health facilities and the community in disease prevention efforts. The activity recommends expanding program coverage, training health cadres, and enhancing monitoring to ensure sustainability and maximize the impact of the FHE program in the future.